2008
DOI: 10.1007/s10552-008-9284-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status in relation to early menarche among black and white girls

Abstract: Objective Early menarche is a risk factor for breast cancer. We investigated the variation in age at menarche by socioeconomic status (SES) and race. Methods A cohort study was conducted on 1,091 black and 986 white girls from the three sites in the United States as part of the NHLBI Growth and Health Study (NGHS), who were aged 9-10 years at baseline and followed through adolescence over a 10-year period with annual exams. Using logistic regression models, we evaluated the nature and strength of associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
102
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 29 publications
13
102
4
1
Order By: Relevance
“…Average age estimates for menstruation in low and middle income countries which may have some relevance for ethnic minority groups included in the current study are largely historical and limited in availability. 40 Similar to our findings, socioeconomic gradients in puberty onset have been shown elsewhere, 12 and two landmark studies suggested that disadvantaged early environments, characterised by some or all of poverty, family conflict, father absence and negative parenting were associated with early onset menstruation. 22 23 Other reports suggest that stressful circumstances just prior to puberty might have the opposite effect, delaying onset, 41 42 but findings from these reports are confounded by co-occurring nutritional stress which makes their interpretation difficult.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Average age estimates for menstruation in low and middle income countries which may have some relevance for ethnic minority groups included in the current study are largely historical and limited in availability. 40 Similar to our findings, socioeconomic gradients in puberty onset have been shown elsewhere, 12 and two landmark studies suggested that disadvantaged early environments, characterised by some or all of poverty, family conflict, father absence and negative parenting were associated with early onset menstruation. 22 23 Other reports suggest that stressful circumstances just prior to puberty might have the opposite effect, delaying onset, 41 42 but findings from these reports are confounded by co-occurring nutritional stress which makes their interpretation difficult.…”
Section: Discussionsupporting
confidence: 88%
“…8 Prior studies, mostly from the USA, have described socioeconomic and ethnic/racial patterning of the onset of puberty. [9][10][11][12][13][14] Given the different historical and geographical patterns of migration to the UK and USA we might not necessarily expect to see ethnic differences in early puberty in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates Ethnicity, 14,22,42,55 socioeconomic status, 15,44,56 family structure, 11,55,57 and birth size 3,11,15,58 are thought to be associated with both AAM and age at FSI but are unlikely to mediate the relationship. Key variables reflecting these constructs were selected from the data collected at baseline and at age 10 years to construct an a priori-adjusted model.…”
Section: Fsi Datamentioning
confidence: 99%
“…Factors regulating AAM are not well understood, but in developed countries, about one-half of the variation in AAM is thought to be genetic. 1,2 Other mediating factors include birth and childhood body size, [3][4][5][6] adiposity, 3,7 growth, [8][9][10] race/ethnicity, [11][12][13] socioeconomic position, [13][14][15][16][17] family relationships and structure, 11,16,18,19 and exposure to childhood adversity and trauma. 20,21 Younger AAM has widely been proposed as a risk factor for early first sexual intercourse (FSI).…”
mentioning
confidence: 99%
“…Early or late menarcheal age has great influence on the health of women. Researchers have found that an early menarcheal age was associated with an increased risk for endometriosis, obesity and type 2 diabetes [1,2,3], as well as several hormone-associated cancers, such as breast cancer, myomatosis, multiple sclerosis, endometrial cancer and uterine leiomyomata [4,5,6,7,8,9], and late menarcheal age was associated with urinary incontinence, senile dementia and osteoporosis [10,11]. …”
Section: Introductionmentioning
confidence: 99%